Sistem Informasi Perpustakaan Jurusan Fisika Universitas Papua Berbasis Web Menggunakan framework Codeigniter 3 : Web-Based Library Information System Of The Department Of Physics, University Of Papua Using The Codeigniter 3 Framework - allo, ronal; Marini, Lion Ferdinand; Suhendra, Christian Dwi (Universitas Papua, 2024)
The library is part of a learning resource for students at the Department of Physics, University of Papua. Because it makes it easier for students to find information or knowledge through the library. With the development of technology, humans think about being able to work more effectively and efficiently, one of which is to make computerized systems and systems. This study aims to create a Library Information system at the Department of Physics, University of Papua in terms of book search, book data collection, member data collection, borrowers and book returns. The method used in designing library information systems is the RAD model, as well as using PHP programming language (PHP Hypertext Preprocessor), MySQL database server and using CodeIgniter Framework. The result of this research is a web-based library information system application that has transaction features, making it easier to collect data on borrowing and returning books, and will improve performance and make it easier to manage book data